AYURVEDIC MANAGEMENT OF SYSTEMIC SCLEROSIS - A SINGLE CASE STUDY - Sreenithya.M; Neelakanta. J. Sajjanar; Sowmyashree.U.P; Gopalakrishna.G (International Journal of Ayurveda and Pharma Research, 2021)
Systemic sclerosis (SSc) is a multisystem autoimmune disorder caused by unknown factors. Which results in fibrosis of the skin, blood vessels, and visceral organs, including the gastrointestinal tract, lungs, heart, and kidneys. One among subset is referred to as diffuse cutaneous scleroderma and characterized by the rapid development of symmetric skin thickening of proximal and distal extremity, face, and trunk. When it affects on musculoskeletal system, the synovium in patients with arthritis is similar to that seen in early rheumatoid arthritis and shows edema with infiltration of lymphocytes and plasma cells. A 35-year-old house wife with this diagnosis came to OPD, which is managed by the principle of Amavata (diseases of connective tissue in Ayurveda) line of treatment. Vaitarana basti and Valuka sweda has done for 7 days with oral medication Vaishwanara churna ½ teaspoon with first morsal of food for 3 times. The QOL (quality of life) has been improved with in 7 days of treatment.